Trading volume, earnings per share and stock returns and their impact on bid-ask spreads on manufacturing industry sector stocks listed on the Indonesia stock exchange 2015-2018 - Dede Djuniardi; Entin Jumantini; Ari Jamhari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This research was to provide empirical evidence regarding The Effect of Trading Volume, Earning Per Share on Stock Returns, and their impact on Bid-Ask Spread in manufacturing companies listed on the Indonesian Stock Exchange. The method of the research used data from 114 companies manufacturing industry sector that was listed on the Indonesia Stock Exchange in 2015-2018. Technique analysis data used path analysis with IBM SPSS Statistics software and hypothesis test used F test, t-test, and Sobel test. Based on the results of the t-test (partial) showed that Trading Volume had a significant positive effect on Stock Returns, Earning Per Share had no significant effect on Stock Returns, Trading Volume had a significant negative effect on Bid-Ask Spread, Earning Per Share had a significant negative effect on Bid-Ask Spread, Stock Returns had a significant negative effect on Bid-Ask Spread. Based on the results of the F test, is shown that Trading Volume and Earning Per Share together have a significant effect on Stock Returns. Trading Volume, Earning Per Share and Stock Returns has a significant effect on Bid-Ask Spread.